ANALISIS PENGARUH SUMBER PENDAPATAN DAERAH TERHADAP BELANJA MODAL DAN PENGARUH BELANJA MODAL TERHADAP BELANJA PEMELIHARAAN DALAM REALISASI ANGGARAN PEMERINTAH KABUPATEN/KOTA DI PROVINSI JAWA TENGAH DAN PROVINSI DAERAH ISTIMEWA YOGYAKARTA TAHUN 2006-2010 - Kurniawati Nursepti Ariyani; Rohmad Yuliantoro (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2012)
The allocation of capital expenditure especially on infrastructure expenditure on local financial budget, is very important, because it can increasing public service. The increase of public service will also increase the own revenues. The increase ot own revenues will endorse the economic productivity. Local goverment also needs transfer fund from the central goverment, for development. It means that capital expenditure is depends on own revenues and transfer fund.Capital expenditure partially used to funding maintenance expenditure. It means the policy of local goverment on the spending of capital expenditure will effects on maintenance expenditure. The research aimed to see the effect of resource of revenues that consist of own revenues and transfer fund to capital expenditure, and the effect of capital expenditure to maintenance expenditure in regions/municipals in Central Java and Yogyakarta province.The result shows that own revenue is effecting the capital expenditure, but transfer fund is not effected by the capital expenditure, the capital expenditure is effecting the maintenance expenditure.